Peristaltic flow with thermal conductivity of H2O + Cu nanofluid and entropy generation - Noreen Sher Akbar (Results in Physics, 2015)
In this article, it is opted to investigate the effects of entropy and induced magnetic field for the peristaltic flow of copper water fluid in the asymmetric horizontal channel , the mathematical formulation is presented, the resulting equations are solved exactly. The obtained expressions for pressure gradient , pressure rise, temperature, axial magnetic field, current density, velocity phenomenon entropy generation number and Bejan number are described through graphs for various pertinent parameters. The streamlines are drawn for some physical quantities to discuss the trapping phenomenon.